Systematic Review of Factors Associated with the Utilization of Radical Cystectomy for Bladder Cancer - Williams, Stephen B.; Hudgins, Hogan K.; Ray-Zack, Mohamed D.; Chamie, Karim; Smaldone, Marc C.; Boorjian, Stephen A.; Daneshmand, Siamak; Black, Peter C.; Kamat, Ashish M.; Goebell, Peter; Seiler, Roland; Schmitz-Drager, Bernd; et al. (European Urology Oncology, 2019)
CONTEXT: Despite established guidelines for the treatment of muscle-invasive bladder cancer, it has been reported that radical cystectomy (RC) is markedly underused, especially among patients of advanced age and those with higher comorbidity burden and lower access to care. Understanding the interactions between patient, provider, and hospital factors may inform targeted interventions to optimize RC utilization. OBJECTIVE: To systematically review the literature regarding factors associated with RC utilization. EVIDENCE ACQUISITION: A systematic search was conducted using Ovid and Medline according to Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines to identify studies between 1970 and 2017 reporting on RC utilization. Prospective and retrospective studies were included. EVIDENCE SYNTHESIS: There are no published randomized control trials on RC utilization. Variations in study quality and design precluded a formal statistical meta-analysis. RC receipt significantly depended on patient, provider, and hospital factors. Patient factors associated with lower RC use included advanced age, African American and Hispanic race/ethnicity, higher comorbidity burden, unmarried marital status, higher tumor stage and grade, and lower socioeconomic status. Provider factors associated with underutilization included lower surgeon volume and a metropolitan location. Finally, hospital factors associated with lower RC use included low hospital volume, nonacademic affiliation, and hospital location in the Midwest. CONCLUSIONS: RC is reportedly underutilized. We found that age, race, marital status, socioeconomic factors, cancer severity, comorbidity burden, surgeon volume, and facility type and location significantly determined RC receipt. Improved understanding of the varying contributions of the risk factors according to patient, provider, and hospital determinants may assist in developing targeted interventions to improve RC utilization. PATIENT SUMMARY: In this review we explored the clinical evidence for factors predicting the utilization of radical cystectomy for muscle-invasive bladder cancer. Many factors related to the patient, provider, and hospital determine whether patients receive this guideline-recommended treatment. However, there remains a lack of understanding on characterization and targeted interventions according to these levels, which may improve use.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Predictors; Radical cystectomy; Use; Utilization